Intenzivnost in načini vključevanja slovenskih podjetij v globalne verige vrednosti - Burger, Anže (IB revija (Ljubljana), 2016)
The effectiveness of the integration of Slovenian companies into international trade is increasingly dependent on the intensity and quality of their integration into the global value chains (GVCs) of other companies and on the creation of their own GVCs. The share of exports of intermediate products in overall Slovenian exports is steadily rising, which is in line with global patterns of international production and trade and indicates the increasing importance of GVC integration for Slovenian exports. As far as the modes of integration into GVCs are concerned, which include vertical integration via inward and outward FDIs versus integration on a contractual basis, the data shows that Slovenian exports of final products are much more vertically integrated than their intermediate product counterparts. It can therefore be concluded that, in times of economic recession, vertical integration facilitates greater export stability than contractual integration for exports of final products. The two key factors that determine the intensity of any aspect of a company's integration into GVCs are its productivity and general export propensity. As expected, the likelihood that a company will vertically integrate into GVCs, i.e. for the purpose of imports and exports via their own subsidiaries or parent companies abroad, depends primarily on whether they have subsidiaries abroad or are owned by a foreign parent company. Other factors that increase the probability of a company's vertical integration into GVCs are average salary as a proxy for skill level, capital intensity, process innovations and innovation cooperation. Product innovations, on the other hand, increase the probability of contractual integration into GVCs.
Keywords: Slovenia; Slovenija; mednarodna trgovina; podjetja; globalne verige vrednosti; proizvodni procesi; vmesni proizvodi